Pembuatan Aplikasi Try Out Cat (Computer Assisted Test) Penerimaan Pegawai Negeri Sipil Bidang Tes Intelegensi Umum Berbasis Desktop - Saputro, Agung Dwi; Kuddi, Bobi Frans (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Civil servants are a job with a large demand, this can be seen from the data from the State Civil Service Agency (BKN) each year. Data from the State Civil Service Agency shows that from 2017 to 2018 there was an increase in the number of participants, namely as many as 2,433,655 in 2017 and to 4,436,694 in 2018. However, to become a civil servant there are many stages of tests that must be passed starting from the Selection administration to the final stage of filing. However. The Computer Assisted Test (CAT) stage is the most difficult stage because participants are required to work on questions using a computerized system with a short time limit. The purpose of this research is to create a program that is similar to the CAT program. The convenience provided is the availability of a try out application that can be accessed at any time, besides that, prospective participants are made familiar with the original CAT application because the try out application is made as closely as possible.